Pentingnya Persiapan Diri untuk menjadi Seorang Pemimpin: Studi Hermeneutik Berdasarkan Kisah Samgar dalam Hakim-Hakim 3:31 - Pattinaja, Aska Aprilano; Talilah, Steven Robertho (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Samgar b. Anath is an unpopular judge in the history of the judges. His story only appears in two verses in the Bible, Judges 3:31 and Judges 5:6. The very limited story of Samgar b. Anat makes him less popular and desirable to discuss.   Therefore, this study aims to explore the origin and leadership of Samgar b. Anath as a judge over Israel, which has an impact on preparing oneself to be a leader.   The research used descriptive qualitative method, hermeneutic study and found three important lessons that impacted the preparation of being a leader, namely: first, leaders must prepare themselves well, because God can use anyone to be His chosen one; second, leaders must have a strong sense of confidence; third, leaders must rely on God. This research is very important and serves as input for leaders to decide to live right and make a difference, as well as develop the resources available to them.